Advances and prospects of precision nanomedicine in personalized tumor theranostics - Mao, Yuhang; Xie, Juanping; Yang, Fang; Luo, Yan; Du, Juan; Xiang, Hong (Frontiers in Cell and Developmental Biology, 2024)
Tumor, as the second leading cause of death globally, following closely behind cardiovascular diseases, remains a significant health challenge worldwide. Despite the existence of various cancer treatment methods, their efficacy is still suboptimal, necessitating the development of safer and more efficient treatment strategies. Additionally, the advancement of personalized therapy offers further possibilities in cancer treatment. Nanomedicine, as a promising interdisciplinary field, has shown tremendous potential and prospects in the diagnosis and treatment of cancer. As an emerging approach in oncology, the application of nanomedicine in personalized cancer therapy primarily focuses on targeted drug delivery systems such as passive targeting drug delivery, active targeting drug delivery, and environmentally responsive targeting drug delivery, as well as imaging diagnostics such as tumor biomarker detection, tumor cell detection, and in vivo imaging. However, it still faces challenges regarding safety, biocompatibility, and other issues. This review aims to explore the advances in the use of nanomaterials in the field of personalized cancer diagnosis and treatment and to investigate the prospects and challenges of developing personalized therapies in cancer care, providing direction for the clinical translation and application.